Nowe oblicza adaptacji tekstu w mediach cyfrowych. O powieści hipertekstowej popołudnie, pewna historia Michaela Joyce’a - Pisarski, Mariusz (Slavia Occidentalis, 2011)
Working on a novel and its adaptation, in the case of hypertext, i.e., a novel that branches and develops on demand, that is written and read on the computer screen, requires and itself creates new roles. The translation begins to embrace new domains. The first translation of a hypertext novel in the Slavic countries popołudnie, pewna historia (“afternoon: a story”) by Michael Joyce presents translation as the transfer not only of language elements of a given medium but also of a reader’s computer code, operating system and interface. A role of a translator, an editor and a publisher changes radically, whereas a reader faces new challenges in which authors of adaptations must play an assisting role. A literary message in new media appears as a multilayer arrangement of diversified, parallel utterances of a much bigger than traditionally, range of connotations. The project discussed by the author of the article, heralds the contemporary and the future literary productions in the epoch called “post-PC” (PC – personal computer). In such circumstances, the authors of translations must look far beyond the horizon of the text in order to return to that text and show it properly.